Penyuluhan UMKM Di Era New Normal Dengan Memprioritaskan Ekonomi Digital Marketing - Elvitrianim Purba; Sri Trianovie; Syuhada (HIMPUNAN DOSEN GEMILANG INDONESIA, 2023)
In the new normal era, it is a stage for the government and society to solve economic problems that occur at all levels of society. So by taking advantage of this new normal situation, we intercollegiate lecturers in Labuhanbatu have conducted MSME outreach activities aimed at reviving and increasing the spirit of entrepreneurship by utilizing social media as one of the strategies for digital marketing in Bulungan Village. This counseling was attended by 20 residents of Marbau MSME owners, Bulungan Village, Marbau District, North Labuhanbatu District. By carrying out MSME counseling, we Lecturers across Higher Education concluded that the MSME counseling that we provided to MSME owners in Bulungit Village, Marbau District, North Labuhanbatu Regency had an economic impact on MSME actors increasing so that they were able to maintain their lives.